World Famous Scientist Lotfi A. Zadeh Azerbaijan "Era": In the Context of History Philosophy - Khatira Guliyeva (Journal of Pedagogy and Education Science, 2023)
One of modern science's most important tasks is to research and examine the era, perspective and philosophical views of the genius scientist Lotfi A. Zadeh, who served science for 70 years and raised it "from earth to the universe" in the context of the historical philosophy. This article describes the "era" of  Lotfi A.  Zadeh, which started in Azerbaijan and ended with his eternity in Azerbaijan. This article is the part monograph of the Author of the article "Lotfi A. Zadeh. Of course, the main part of Lotfi A. Zadeh's "era" passed far away from Azerbaijan - to the United States. After a long break, in 1965, when he came to Russia for a conference, he made a short visit to Azerbaijan. The genius scientist's first and last live visit to Azerbaijan took place in 2008,  which the Author of the article called this visit "21st century. The peak of Lotfi A. Zadeh  Azerbaijan and Azerbaijanis "era". And the last - a genius scientist - returned to his native land once and for all when he died in 2017 at 96. This entire period is evaluated in the context of the philosophy of history in the article.